Teknologi Elektronis Pengkajian Nyeri Kronis pada Anak-anak dan Remaja: Electronic Technology for Chronic Pain Assessment in Children and Adolescents - Dwi Novrianda (Fakultas Keperawatan Universitas Andalas, 2012)
Chronic pain in children and adolescents is a problem that can affect every aspect of individual functions. The big change in the quality of life of a child dealing with chronic pain. Impaired function generally occurs i.e., sleeping, employment, social functioning, and daily activities. Monitoring of chronic pain should be a concern to the clinician in monitoring the way the pain so as to provide effective care and treatment. Pain is a subjective thing and needs expressed by individuals who experience such pain. One method of assessment of chronic pain in children and adolescents that can be applied in clinical practice is the use of electronic pain diary that combines handheld hardware technology advances such as smartphones and PDAs with pain assessment software program innovations that have proven their quality index. In order to use this application to apply the necessary attention to the ethical aspects, financial aspects of the tools and training, aspects of change in perspective on the importance of understanding the chronic pain patient in order to change behavior.